INTRODUKSI FERMENTOR HORIZONTAL BERPENGADUK DILENGKAPI LAMPU UV-C DI UMKM SAGUMBI UNTUK PRODUKSI PATI SAGU TERMODIFIKASI - Abadi Jading; Paulus Payung; Eduard Fransisco Tethool (Universitas Jenderal Soedirman, 2021)
The development of modified starch made from raw sago is intended to meet the availability of starch that can produce processed food products with starch raw materials and flour based on local resources. The purpose of this activity is to produce a modified sago starch technology package at UMKM SAGUMBI by introducing a stirred horizontal fermentor machine equipped with UV-C (FHP-UVC) lamps integrated with rotary drum vacuum filter dewatering type for modified starch production in West Papua. The approach method used is the dissemination of the FHP-UVC machine, training on the operation of the FHP-UVC machine, and mentoring at UMKM SAGUMBI. The results of the training show that participants understand the parts, how to operate, and how to maintain FHP-UVC machines, and understand how to make sago starch slurry. The technical-economic impact after this dissemination activity was the availability of a horizontal fermentor stirring machine with a 180 W UVC lamp with a capacity of 50 lt of starch slurry per process, so that partners were able to produce modified sago starch. This has a significant impact on increasing the income of business partners, and sago farmers around the partner locations.Keywords: FHP-UVC machine, modified starch, sago, UMKM SAGUMBI